Efficient decolorization and detoxification of azo dyes by a halotolerant yeast Meyerozyma guilliermondii A3 with relatively low external carbon source. (June 2022) - Li, Jiamin; Wang, Meining; Fu, Xinmei; Cui, Jingru; Feng, Yue; Tan, Liang
Abstract: Decolorization and detoxification of azo dyes by a newly isolated halotolerant yeast was investigated in the present study. This work included isolation and identification of the halotolerant yeast, optimization of its growth and decolorization conditions, proposal of dye decolorization pathways, and analysis of the transcriptomic responses to dye and salt stress. The results showed that a halotolerant yeast which was capable of efficiently decolorizing various azo dyes under saline conditions was isolated and identified as Meyerozyma guilliermondii (strain A3). The optimal conditions for dye decolorization and yeast growth were as follows: glucose (sucrose was also suitable) ≥1.0 g/L, (NH4 )2 SO4 ≥ 0.2 g/L, yeast extract ≥0.04 g/L, salinity (NaCl concentration) ≤30.0 g/L, temperature 30-35 °C, pH 6.0–7.0 and rotation speed ≥160 rpm. The target dye Acid Red B (ARB) was significantly detoxified by the yeast A3 intracellularly through the processes including cleavage of azo bonds, ortho-hydroxylation (monooxygenation pathway), oxidative desulfurization/deaminization, ring opening of substituted naphthalene, and TCA cycle. Genes encoding oxidoreductases and sugar transporters were universally up-regulated under dye stress, and those encoding cell wall regulators were also up-regulated under salt stress. Meanwhile, genes encoding oxidoreductases and sugar transporters were universally down-regulated under salt stress. Graphical abstract: Unlabelled Image Highlights: First report on azo-degradation by a halotolerant Meyerozyma guilliermondii yeast. M. guilliermondii A3 used only 1.0 g/L glucose/sucrose for fast decolorization. M. guilliermondii A3 significantly detoxified Acid Red B (ARB). Possible degradation pathway of ARB by M. guilliermondii A3 was also proposed. The transcriptomic responses to dye and salt stresses were analyzed.